The Peninsula Shale Renosterveld of Devil's Peak: phytosociology, system drivers and restoration potential - Cowan,Oliver Silver (Department of Environmental and Geographical Science, 2014)
Peninsula Shale Renosterveld is a poorly understood and critically threatened vegetation type with 87% of its original extent transformed and the remaining fragments restricted to the area surrounding the Cape Town city bowl. A substantial portion of Peninsula Shale Renosterveld is situated in the Groote Schuur Estate, currently conserved within the Table Mountain National Park. Due to a history of diverse land-use impacts, what remains today is a complex mosaic of alien invasive species and indigenous vegetation in various states of degradation. As a result of the substantial transformation, it is evident that to improve the conservation value of this highly threatened vegetation type, restoration is required. However, as many restoration projects fail as a result of a poor understanding of the ecosystem dynamics in which they are operating in, it is imperative that prior to initiation data is collected from the site. To enhance the understanding of the ecosystem drivers of Peninsula Shale Renosterveld with a view to evaluate restoration potential and inform future restoration initiatives a short-term, detailed analysis of four typical vegetation states found within the study area was undertaken. This was accomplished through a detailed land-use history analysis focusing on the practices which have brought the system to its current position; a phytosociological survey investigating the contemporary state of the study area; and an examination of the health of the seedbank through a greenhouse experiment to ascertain whether it could prove a useful asset in future restoration initiatives. The results show how historical drivers have created a novel ecosystem with vegetation states ranging from relatively healthy Renosterveld vegetation, indigenous vegetation requiring intervention to maintain its integrity, and regions of the study area where only active restoration efforts can return the degraded vegetation to functional Peninsula Shale Renosterveld. Despite this novel ecosystem, each vegetation state broadly fits into hypothetical Renosterveld ecosystem driver models, thus providing data for future restoration requirements. The seedbank diversity was found to be poor, dominated by alien ephemeral species and unlikely to assist in restoration efforts. The results also suggest the soilstored seedbank in Renosterveld may not be of great importance for succession post-disturbance. In addition to providing valuable baseline data and enhancing the knowledge on drivers within Peninsula Shale Renosterveld, the project recommends and provides motivation for future management actions that will enable the restoration of this critically endangered vegetation type.